Early democratization, corruption scandals and perceptions of corruption: evidence from Mexico. Issue 2 (17th February 2021) - Petersen, German
ABSTRACT: The most accepted theory of the relationship between democratization and perceptions of corruption is the curvilinear theory. The theory states that in early democratization corruption increases, then it reaches a ceiling, and finally it begins falling, forming an inverted U. The increase in perceptions of corruption in early democratization has been associated with an increase in actual acts of corruption. This paper claims that the inverted-U relationship between democracy and corruption may or may not be explained by corruption, but it is surely explained by corruption scandals. Using evidence from the 32 Mexican states over the period from 2000 to 2018, the article substantiates that early democratization, particularly first turnovers, significantly and robustly increases corruption scandals. In turn, corruption scandals have an influence on perceptions of corruption. Ultimately, early democratization moves perceptions of corruption through the mechanism of corruption scandals, with the role of actual acts of corruption being an open question.